2011
DOI: 10.1093/infdis/jir424
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9 and CXCL10 Chemokines as Predictors of Liver Fibrosis in a Cohort of Primarily African-American Injection Drug Users With Chronic Hepatitis C

Abstract: CXCL9 (monokine induced by IFN γ [Mig]) and CXCL10 (interferon [IFN] γ-inducible protein 10 [IP-10]) have been associated with hepatic fibrosis in predominantly white hepatitis C virus (HCV)-infected patients. We investigated their potential as noninvasive markers of hepatic fibrosis and fibrosis progression in African-American patients. Peripheral chemokine levels were measured in 115 HCV-infected patients within 4 months of liver biopsy; patients underwent a second biopsy after 3-5 years. CXCL10 levels appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 13 publications
(21 reference statements)
2
53
0
Order By: Relevance
“…CXCR3 ligands have been extensively investigated in animal studies [6,10,13,15,23,34], as well as in humans with liver disease [5,9,11,12,16,18,26,27,35]. Different studies have assessed a relationship between CXCR3 ligands and fibrosis and hepatic injury [8][9][10][12][13][14][15][16][17][18], angiogenesis [6], and complications of liver cirrhosis [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR3 ligands have been extensively investigated in animal studies [6,10,13,15,23,34], as well as in humans with liver disease [5,9,11,12,16,18,26,27,35]. Different studies have assessed a relationship between CXCR3 ligands and fibrosis and hepatic injury [8][9][10][12][13][14][15][16][17][18], angiogenesis [6], and complications of liver cirrhosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…These processes themselves are at least partly initiated and modulated by chemokines [3,4]. In particular, CXCR3 ligands, especially CXCL9, are increased during liver diseases [5][6][7][8][9][10][11][12] and are functionally linked to hepatic injury, inflammation, fibrosis, [8][9][10][12][13][14][15][16][17][18], angiogenesis [6] and complications of cirrhosis [19]. Liver resident cells, such as hepatocytes, Kupffer cells and hepatic stellate cells were found to represent a major source of CXCR3 ligands in the liver [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of IP-10 levels are known to be associated with reduced rates of sustained virological response during treatment of HCV with pegylated (PEG)-IFN/ribavirin (RBV) [37,[47][48][49] HIV-1/HCV coinfection [38,50] and reduced spontaneous clearance to acute infection [51]. Further, high IP-10 levels have been associated with greater inflammation and liver fibrosis [48,49] even in a cohort of African-American injection drug users with chronic HCV [52]. Thus, these increased levels of IP-10 within the HIV-1/HCV co-infected individuals in the CARES Cohort could likely be a marker of reduced response to therapy, immunologic dysfunction ultimately leading to an accelerated progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have been showed that the levels of the IFN-γ inducible chemokines CXCL9-11 are significantly up-regulated in the serum and livers of patients with various liver disease [1,[12][13][14]. The high levels of CXCL9-11 have been found to be independently related to the development of clinically hepatic disease [15,16]. According to some studies, elevated serum and intrahepatic CXCL9 and CXCL10 expression levels have been reported as important prognostic and predictive biomarkers of progressive liver injury [17][18][19][20], CXCL11, which is also expressed by hepatocytes, involves in pro-inflammatory T cells recruitment and differentiation [7].…”
Section: Introductionmentioning
confidence: 99%